Long discontinuous carbon fibre/polypropylene composites for high volume structural applications - Harper, L.T.; Burn, D.T.; Johnson, Michael S.; Warrior, N.A. (Sage, 2017)
A processing route is presented to manufacture discontinuous carbon fibre reinforced polypropylene (CF.PP) composites, using much longer fibre lengths (25mm) and higher volume fractions (up to 45%) than previously reported in the literature. Carbon fibre tows are coated with different ratios of polypropylene, blended with a maleic anhydride coupling agent, to investigate the influence of the interfacial shear strength at the microscale on the macroscale composite properties. Improvements in the tensile performance at the macroscale (70% increase) are not as high as those reported for the interfacial shear strength at the microscale (300%), following the addition of the coupling agent. Consequently, the tensile strength of the CF.PP material is only 45% of values reported for carbon fibre/epoxy systems, however, the tensile stiffness is comparable. This demonstrates the potential for using CF.PP for structural applications, following further process optimisation to overcome the current high levels of porosity (3.3% at 0.45Vf) to improve the tensile strength.